SINERGITAS DALAM PELAKSANAAN PENANGGULANGAN KEMISKINAN - Sopandi, Andi (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2012)
Poverty reduction synergy is a tactical step in reducing the poverty rate, especially in Indonesia. The main prerequisites are (1) how to explore the potential of community in the form of social capital (Social Capital), (2) Building Self-Relience; (3) Creating Self-Supporting and (4) Sustainable Program . The four elements above are the basic keys in efforts to tackle poverty